2010
DOI: 10.1016/j.nmd.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Revertant fibres and dystrophin traces in Duchenne muscular dystrophy: Implication for clinical trials

Abstract: Duchenne muscular dystrophy (DMD) is characterised by the absence of dystrophin in muscle biopsies, although residual dystrophin can be present, either as dystrophin-positive (revertant) fibres or traces. As restoration of dystrophin expression is the end point of clinical trials, such residual dystrophin is a key factor in recruitment of patients and may also confound the analysis of dystrophin restoration in treated patients, if, as previously observed in the mdx mouse, revertant fibres increase with age. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
63
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 40 publications
2
63
1
Order By: Relevance
“…The expression of very low levels of trace dystrophin in patients with DMD has been observed before [1], [2], but emerging methodologies on imaging and quantification of expression levels have shown that trace dystrophin is expressed more commonly in nearly all fibers in the majority of DMD muscle biopsies [3][7]. The incidence of revertant fibers that express relatively high levels of dystrophin is generally low (<5%) and appears to be dependent on the deletion and can reach 14% [6], [7]. Trace dystrophin and revertant fibers can be recognized and accounted for in immunofluorescence analysis (IFA) of muscle biopsy cross-sections.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The expression of very low levels of trace dystrophin in patients with DMD has been observed before [1], [2], but emerging methodologies on imaging and quantification of expression levels have shown that trace dystrophin is expressed more commonly in nearly all fibers in the majority of DMD muscle biopsies [3][7]. The incidence of revertant fibers that express relatively high levels of dystrophin is generally low (<5%) and appears to be dependent on the deletion and can reach 14% [6], [7]. Trace dystrophin and revertant fibers can be recognized and accounted for in immunofluorescence analysis (IFA) of muscle biopsy cross-sections.…”
Section: Introductionmentioning
confidence: 94%
“…One image analysis method determined the average dystrophin intensity from all fibers in an image that co-localized with a spectrin signal in a software-generated mask defining the sarcolemmal area [4]. Another method assessed dystrophin expression by manually placing circles on randomly selected areas of the sarcolemma of a selected number of fibers per biopsy and measured the maximum membrane intensity within that circle [5], [6]. It has been reported that the intensity of dystrophin may vary between fibers in a healthy control muscle [4], [5] and that this variability is even more pronounced in BMD and DMD muscle [2], [3], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In one of these (patient 2 in that report) the response consisted of CD4 + cells, whereas in the other (patient 4) it was mediated by CD8 + cells. It had been postulated that such priming was unlikely, due to the presence of revertant fibers in many patients (estimated, using different degrees of sensitivity in the analysis, as occurring between 0.01 and 47% of patients with DMD [Kissel et al, 1991;Fanin et al, 1992Fanin et al, , 1995Klein et al, 1992;Thanh et al, 1995;Uchino et al, 1995;Winnard et al, 1995;Arechavala-Gomeza et al, 2010]). In these fibers, dystrophin protein is expressed because of secondary mutations within the individual muscle fibers-most commonly, altered splicing that restores the reading frame and allows translation of exons downstream of the primary mutation.…”
Section: Introductionmentioning
confidence: 99%
“…It had been postulated that such priming was unlikely, due to the presence of revertant fibers in many patients (estimated, using different degrees of sensitivity in the analysis, as occurring between 0.01 and 47% of patients with DMD [Kissel et al, 1991;Fanin et al, 1992Fanin et al, , 1995Klein et al, 1992;Thanh et al, 1995;Uchino et al, 1995;Winnard et al, 1995;Arechavala-Gomeza et al, 2010]). In these fibers, dystrophin protein is expressed because of secondary mutations within the individual muscle fibers-most commonly, altered splicing that restores the reading frame and allows translation of exons downstream of the primary mutation.…”
mentioning
confidence: 99%